(untitled) - Furnivall, J. S. (Cambridge [Eng.], 1944)
Chapter I: Indonesia, to 1600, Chapter II: The East India company, 1600-1800 ..., Chapter XIII: Plural economy
Keywords: Indonesia,Indonesia,Indonesia,Indonesia,Indonesia; History,Lịch sử,Economic conditions,Economic conditions,Điều kiện kinh tế